Acute Kidney Injury in Patients of Intensive Care Unit (Anwer Khan Modern Medical College Journal, 2017)
Background: Acute Kidney Injury (AKI) is a common complication in patients admitted to the intensive care unit (ICU) and numerous causes are responsible for its development. The aim of the present study is to assess the incidence, risk factors, and outcome of patients who develop AKI in our ICU.Methodology: This study was conducted by the Department of Nephrology, Anwer Khan Modern Medical College Hospital (AKMMCH), a tertiary level center of Dhaka, during the period of January 2015 to December 2015. This is a Cross Sectional Descriptive type of Observational study on patients of Acute Kidney Injury (AKI) admitted to Intensive Care Unit (ICU) of AKMMCH.Result: A total number of 271 patients were admitted. Out of 271 patients, 59 (21.77%) patients with AKI who met our study requirements were included in the study and were evaluated. Among 59 patients 32 (54.23%) were males and 27 (45.77%) were females, with a male to female ratio of 1.19:1. The cause of admission were Diabetes mellitus with complication 11 (18.64%), Hepato-renal syndrome 10 (16.94%), Malignancy 7 (11.86%), Septicaemia 6 (10.18% ), Pneumonia 6 (10.18%), Intra-uterine death (IUD) 5 (8.48%) and others (Acute Myocardial Infarction, Non ST segment Elevated MI, Cerebro Vascular Disease, Gullain Burre Syndrome, Laparatomy, Type I and Type II Respiratory failure) 14 (23.72%). According to RIFLE's criteria most of the patients were from Injury group 32 (54.23%). Next to this, was Risk group 17 (28.83%) and in Failure, Loss and ESRD group were 7 (11.86%), 1(1.69%) and 2 (3.39%) accordingly. Regarding biochemical abnormality, mean Serum creatinine was 3.68 ± 2.15 and that of Urine output, HbA1C and HCO3 level ( in ABG ) were 4.57 ± 8.89, 6.91±1.4 and 17.14 ± 3.8 respectively. Out of 59 patients 10 (16.95%) needed Haemodialysis. According to RIFLE's criteria 7 (70%) were from Failure group, 1 patient from Loss group and 2 from ESRD group who received haemodialysis. 72.88% (43) patients improved, out of which 57.62% (34) got discharged from ICU after full recovery. 6.48% (4) patients expired and 3.38% (2) turned into ESRD and advised for regular haemodialysis.Conclusion: The incidence of AKI is high in patients admitted to ICU, and the development of AKI is associated with poor outcome and reduced survival. AKI significantly increases the duration of ICU stay, and this is likely to add to the healthcare burden. Age, gender or the presence of comorbidities do not appear to influence the incidence of AKI in our ICU patients.Anwer Khan Modern Medical College Journal Vol. 8, No. 1: Jan 2017, P 38-44